Structural determinants of the HSP90-Fibronectin interaction and implications for fibrillogenesis - Chakraborty, Abir (Rhodes University, Faculty of Science, Department of Biochemistry and Microbiology)
Thesis embargoed. Release date April 2024.
Keywords: Uncatalogued